2007
DOI: 10.1111/j.1464-410x.2007.6976.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the attitudes to prostate cancer treatment among European male patients

Abstract: OBJECTIVES  To understand the attitudes of patients with prostate cancer toward the disease in general and to the use of hormone therapy as treatment; to assess unmet needs in the management of prostate cancer; and to gauge patient receptivity to a potential 6‐month formulation of a luteinizing hormone‐releasing hormone (LHRH) agonist. PATIENTS AND METHODS  Face‐to‐face interviews, lasting 50 min on average, were conducted during January and February 2007 with 200 European men who had been diagnosed with prost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 18 publications
2
15
0
3
Order By: Relevance
“…Therefore, we have to listen to patients' expectations and include patients' preferences. For instance, when selecting the most appropriate treatment modality, PCa patients treated with luteinizing hormone-releasing hormone agonists indicated that they would prefer fewer injections [35] . In this case the use of a 6-month formulation of a luteinizing hormone-releasing hormone agonist would clearly have an added value.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we have to listen to patients' expectations and include patients' preferences. For instance, when selecting the most appropriate treatment modality, PCa patients treated with luteinizing hormone-releasing hormone agonists indicated that they would prefer fewer injections [35] . In this case the use of a 6-month formulation of a luteinizing hormone-releasing hormone agonist would clearly have an added value.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, these visits may provide patients with comfort, reassurance and a sense of control regarding their disease. To the authors' knowledge, only one previous study has explored this topic specifically and it found a strong patient preference for longer treatment intervals using a qualitative research approach [11]. The objective of the current study was to assess patient preference regarding the length of intervals between treatment and/or clinical control.…”
Section: Introductionmentioning
confidence: 98%
“…The reality is that patients repeatedly cite their health care providers as their most important source of information, and they rely on their specialist to inform them about management options 10,20 . Patient preferences for the communication of an initial diagnosis rely on the "honesty and expertise" of their doctors.…”
Section: Introductionmentioning
confidence: 99%